2021
DOI: 10.26719/emhj.21.051
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and factors associated with metabolic syndrome, south-east Islamic Republic of Iran

Abstract: Background: Metabolic syndrome is an important cause of cardiovascular disease. Mortality from cardiovascular disease is 12.82 deaths/100 000 population in Zahedan, south-east Islamic Republic of Iran. Aims: This study aimed to determine the incidence of metabolic syndrome and its predicting factors in Zahedan city. Methods: All participants without metabolic syndrome in a 2009 study in Zahedan, available in 2017, were included in this study. Metabolic syndrome was diagnosed based on the criteria of several or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
2
4
0
1
Order By: Relevance
“…FBG > 100 mg/dl was associated with about 3% increased risk of MetS. Consistent with our nding, same signi cant contribution of FBG in MetS development was found in a recent study recruiting Iranian participants [23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…FBG > 100 mg/dl was associated with about 3% increased risk of MetS. Consistent with our nding, same signi cant contribution of FBG in MetS development was found in a recent study recruiting Iranian participants [23].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our evidence, a recent cohort study recruiting 2,935 middle-aged Chinese population with 3-year follow-up showed the higher risk of MetS incidence in participants having higher BP in compare to normotensive group (hazard ratio (HR), 1.823; 95% CI, 1.538-2.162) [22]. With respect of the signi cant association between TG and metabolic disorders in our study, investigating the population in south of Iran demonstrated the notable linkage between high TG and MetS burden [23].…”
Section: Discussionmentioning
confidence: 51%
“…According to Figure 1 , the diagnostic criteria for people with MetS were a large wc (94.30%), lowered HDL (80.20%), high blood pressure (71.70%), and elevated blood glucose (69.60%), while elevated triglyceride (40.50%) had the lowest proportion. These results were in conflict with those of this study done by Farmanfarma et al ., 25 which demonstrated that the most common diagnostic criteria for MetS were increased wc and high blood pressure, while lowered HDL was the least common. Furthermore, these findings are consistent with those of another study by Venugopal et al , 26 which indicated that a large wc and low HDL are the most common MetS diagnostic criteria, while elevated blood sugar and high triglyceride are the least common.…”
Section: Discussionmentioning
confidence: 99%
“…In various parts of the world, the incidence of metabolic syndrome (MetS) has been estimated to range from 28 per 1000 people per year to more than 70 per 1000 people per year. Rapid economic development, the rise in popularity of the Western lifestyle, and a lack of physical activity have all contributed to the obesity and type 2 diabetes mellitus (T2DM) epidemics that threaten to spread worldwide ( 2 ). Globally, the prevalence of MetS is rising at an alarming rate and is more common among T2DM patients.…”
Section: Introductionmentioning
confidence: 99%